Cotton-like CNTs/(Ni-P)/S composites with enhanced electrochemical performance of lithium-sulfur battery. (January 2022) - Wu, Yaqin; Luo, Zixiang; Wang, Xuri; Fu, Guoli; Lei, Weixin; Zou, Youlan; Yin, Bingbing; Ma, Zengsheng; Pan, Yong; Jiang, Wenjuan
Highlights: 1 Cotton-like CNTs/(Ni-P)/S composites are prepared in this study. 2 Ni-P alloy nanoparticles deposited CNTs can form a three dimensional conductive framework. 3 The cotton-like composites can effectively improve the electrical conductivity of positive electrode materials, and introduces strong polar adsorption and alleviates the 'shuttle effect'. 4 The CNTs/(Ni-P)/S composites can reach an initial discharge specific capacity as high as 1344.6 mAh g   −   1 at 0.2 C, and the discharge specific capacity remained at 885.6 mAh g   −   1 after 200 cycles. Abstract: Low conductivity of the sulfur cathode and dissolution of lithium polysulfides are main obstacles for the application of lithium-sulfur batteries (LSB). So, cotton-like CNTs/(Ni-P)/S composites are prepared in this study. In the composites, Ni-P alloy nanoparticles are uniformly deposited on the surface of CNTs by electroless nickel plating and forming a three dimensional conductive framework. CNTs/(Ni-P) composites with different Ni-P alloy contents are studied. Then, the CNTs/(Ni-P)/S cathode material are obtained by melting method. The results show that, in the cotton-like composites, CNTs can effectively improve the electrical conductivity of positive electrode materials, and the Ni-P alloy on CNTs introduces strong polar adsorption and alleviates the 'shuttle effect'. In particular, the CNTs/(Ni-P)/S composites can reach an initial discharge specific capacity as high as 1344.6 mAh g  −   1 at 0.2 C, and the discharge specific capacity remained at 885.6 mAh g  −   1 after 200 cycles. Graphical abstract: Image, graphical abstract